Answer:
1). (x² + 5) and (x + 4)
2). (x²- 3) and (x + 11)
Explanation:
We have to determine the factors of the given expression (x³ + 4x² + 5x + 20) by grouping method.
x³ + 4x² + 5x + 20
= x²(x + 4) + 5(x + 4)
= (x² + 5)(x + 4)
Therefore, factors of the given expression are (x² + 5) and (x + 4).
Second expression is (x³ + 11x² - 3x - 33)
Now we will find the factors of this expression by grouping.
x³ + 11x² - 3x - 33
= x²(x + 11) - 3(x + 11)
= (x² - 3)(x + 11)
Therefore, the factors of the given expression are (x² - 3) and (x + 11).